Low‐dose radiation therapy: A new potential treatment targeting amyloid load and neuroinflammation in an AD rat model: Molecular and cell biology/neuroinflammation. (7th December 2020) - Ceyzériat, Kelly; Millet, Philippe; Zilli, Thomas; Frisoni, Giovanni B.; Garibotto, Valentina; Tournier, Benjamin
Abstract: Background: Low‐dose radiation therapy (LD‐RT) has shown to be effective to decrease systemic amyloid load and has an anti‐inflammatory effect in chronic inflammatory pathologies. Consequently, we propose to use LD‐RT to decrease two central hallmarks of AD: amyloid load and neuroinflammation. Our collaborators demonstrated recently that a fractionated protocol (2 Gray in 5 fractions delivered daily) significantly reduced amyloid plaques and improved cognition in an AD mouse model (Marples et al., 2016). The aim of our study is to 1) evaluate the impact of LD‐RT on amyloid load and neuroinflammation in another animal model of AD and 2) compare the efficacy of treatment accounting for the neuropathological stage. Method: We used TgF344‐AD (TgAD) rats developing amyloid pathology and presenting the advantage to develop endogenous tauopathy. Brains were unilaterally exposed to LD‐RT with the same fractionated radiation schedule than our collaborators (2 Gray in 5 fractions daily) at two different pathology stages: at an early (9‐month‐old) or an advanced stage (19‐month‐old). TgAD and WT littermate sham‐treated animals were used as control. At an early stage, the 18kDa translocator protein (TSPO) density in different brain regions (frontal cortex, hippocampus, striatum, cerebellum, brain residues) was measured using ex vivo [I 123 ]‐Clinde binding. Animals underwent behavioral evaluation (general locomotion, working memory) 4 months after LD‐RT performed at an advanced AD stage. The number of amyloid plaques was quantified in the hippocampus on immunostained slices. Result: For the first time, we observed a normalization of TSPO levels in the entire brain (‐52%, p<0.001 ), revealing a strong reduction of neuroinflammation. Interestingly, at an advanced stage, LD‐RT reduces hyperlocomotion (‐44%, p<0.05) and significantly improves working memory (+72%, p<0.05), without modifying the amyloid load. Conclusion: We were able to replicate, in a different animal model, the beneficial effect of LD‐RT on cognition of old animals. This could be mediated by an anti‐inflammatory effect as shown by the TSPO‐signal reduction. The LD‐RT impact on amyloid plaques previously reported could not be confirmed when the pathology has strongly progressed. Longitudinal imaging studies will allow a more in‐depth analysis of the effect of LD‐RT on amyloid and neuroinflammation over the disease course.